Evaluation of Errors in Prescription Writing: A Cross-Sectional Study at Community Pharmacies and Tertiary Care Hospitals of Lahore, Pakistan (Bangladesh Journal of Medical Science, 2019)
Background: Prescription errors often lead to mishaps around healthcare facility that often end up with adverse drug reactions and even some cases death Being in a healthcare facility the patient should have full confidence in the health care providers and not have to worry about minor mistakes leading to a possible lethal one.Aim and objective: The aims and objectives of our study is to evaluate the prescription writing errors in different community pharmacies and tertiary care hospitals also to assess the knowledge of patients regarding their disease and treatment.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.260-266